Clean-Development Investments An Incentive-Compatible CGE Modeling Framework - Böhringer, Christoph (The World Bank, 2013)
The Clean Development Mechanism established under the Kyoto Protocol allows industrialized Annex I countries to offset part of their domestic emissions by investing in emissions-reduction projects in developing non-Annex I countries. Computable general equilibrium analysis of the Clean Development Mechanism's impacts so far mimics the Clean Development Mechanism as a sector emissions trading scheme, thereby overstating its potential to save climate change mitigation costs. This study develops a novel approach that represents the Clean Development Mechanism more realistically by compensating Clean Development Mechanism implementing sectors for additional abatement cost and by endogenizing Clean Development Mechanism credits as a function of investment. Compared with previous representations, the proposed approach is more consistent in its incentive structure and investment characteristics at the sector level. An empirical application of the new methodology demonstrates that the economy-wide cost savings from the Clean Development Mechanism tend to be lower than suggested by conventional modeling approaches while Clean Development Mechanism implementing sectors do not lose in output